Food Networks and Agroecology in the Province of Trento – Italy - Carrieri de Souza, Marina; Rover, Oscar José; Forno, Francesca (Frontiers in Sustainable Food Systems, 2023)
As the hegemonic food system is unsustainable in socio-environmental terms, over the last few decades, the search for new forms of food supply has fostered alternative food networks (AFN). Civic Food Networks (CFNs) are a particular subset of AFNs that strongly emphasise the citizenship of the actors involved, including farmers, and their active engagement in the agrifood system. Our objective was to identify CFNs within the studied territory, evaluating farmers' participation, and to answer if the CFNs are contributing to the promotion of agroecology. The research comprises a case study in the province of Trento (Italy). We used direct and participant observation, databases consulting, document analysis, and interviews with key players and organic farmers linked to short food supply chains (SFSC). We evaluated the contributions to the promotion of agroecology through ecological and socioeconomic elements: biodiversity, efficient use of resources and self-consumption. We have identified the presence of initiatives that act by promoting discussion spaces and stimulating the construction of experiences of a SFSC. Those initiatives have provided space for the formation of new networks; created opportunities for new relationships, production and consumption networks. However, organisational structures that favour monocultural systems and commercialisation in long chains prevail in the territory and hinder these innovations. Though the collective organisations of farmers, outside the formal cooperatives, are still developing, farmers are often individualised and with little active participation in decision-making processes within the territory. This study identified an embryonic CFN that showed positive indicators of agroecology for all the analysed aspects. However, the differences were not as significant when compared to other farmers who also participate in SFSC. This research reinforces that there is a potent stimulus to promote agroecology, from the maintenance and encouragement of short food supply chains that are proponents of agrobiodiversity, to the maintenance of family farmers' livelihoods. CFNs have the potential to empower rural actors by providing them with greater participation and autonomy in the agrifood system. However, strengthening these networks remains a challenge, as it requires stimulating social organisation and fostering the integration of various actors within the territory, including rural stakeholders.